Supervision modules to support educators in collaborative teaching : helping to support & maintain consistent practice in the field - Lubniewski, Kathryn L.; Cosgrove, Debbie F.; Robinson, Theresa Y. (Emerald Publishing Limited : Information Age Publishing, Inc., 2019)
The classroom teacher in the 21st century is no longer a solo practitioner. What can school leaders use to facilitate on-going, job-embedded, intentionally focused professional development that is unique to the collective needs of teacher pairs and teams as they work together? What can teacher preparation supervisors provide to support teacher candidates and cooperating teachers as they plan, teach, and assess student learning in a co-teaching context?Supervision Modules to Support Educators in Collaborative Teaching is a research-based supervisory handbook designed to promote on-going teacher reflection and development in collaborative teaching contexts. It is a tool for school leaders and teacher preparation supervisors to use for in-service and pre-service teacher development at all grade levels PK-12.The handbook's many resources provide practical guidance for meaningful teacher development that is field-based, relevant to daily teacher work, and artfully presented to build collaboration among teachers as they reflect and learn together. Unique to this approach is that school leaders and supervisors learn alongside teachers and teacher candidates as relevant topics are explored. The handbook contains a collection of eighteen interactive, activity-based modules that focus on topical content knowledge and productive teaching practices. Embedded in the modules are pair and team activities that address problem-solving, dimensions of collaborative teaching, communication and collaboration skill development, understanding of diversity, cultural responsiveness, and shared understanding of evidence-based practices.This resource is easy to use. Once school leaders and supervisors select a module topic to address the needs of a particular pair or team, they are supported with foundational knowledge of the most current research on the topic, discussion questions about the topic, suggestions of productive practices, questions to deepen personal and group understanding, reflective professional growth activities, critical analysis of teaching scenarios, and monitoring, follow-up, and goal setting strategies. Modules can be used in any order and include reproducible materials for pairs and teams to use as they collaborate and grow professionally.
Keywords: Teaching teams.; Teachers -- Training of.; Education -- Professional Development.; Teacher training.; elektronické knihy; electronic books